Prevalence and treatment outlines for Carrion’ disease (human bartonellosis) in an Amazonas’ district - Romaní Romaní, Franco (2008)
Objectives: To determine the frequency of Bartonellosis in the district of Ocalli,Luya, Amazonas, and to describe treatment outlines at the Ocalli’s Health center.Design: Observational, transverse and retrospective study. Setting: District ofOcalli, province of Luya, department of Amazonas. Patients: Persons with Carrion’sDisease. Interventions: Review of acute anemic febrile records and follow-up ofBartonellosis cases at Ocalli’s Health Center between January 1998 and December2008. Main outcome measures: Prevalence and treatment outlines for Carrion’sDisease. Results: In 111 registered cases of Bartonellosis the average age was15,7 years. The most affected age group was from 2 to 7 years with 47 (42,3%)patients; 61 (54,9%) patients were female. The prevalence was 25,4 cases per1000 and the death rate 2,7%. In the acute phase, 82 (73,9%) patients wereregistered, other 12 (10,8%) had acute complicated Bartonellosis, 14 (12,6%)had the eruptive phase and 3 (2,7%) were probable cases. Most patients with acutenon-complicated Bartonellosis were treated with chloramphenicol (53,6%) andciprofloxacin (44%) and the eruptive phase with rifampicin. Conclusions: Carrion’sDisease is endemic in Ocalli’s district, Luya province high forest. It mainly affectedthe pediatric age. The antibiotic most used in the acute phase was chloramphenicoland ciprofloxacin, and rifampicin in the eruptive phase.